2021
DOI: 10.2196/24955
|View full text |Cite
|
Sign up to set email alerts
|

Using an mHealth App (iGAM) to Reduce Gingivitis Remotely (Part 2): Prospective Observational Study

Abstract: Background Gingivitis is a nonpainful, inflammatory condition that can be managed at home. Left untreated, gingivitis can lead to tooth loss. Periodic dental examinations are important for early diagnosis and treatment of gum diseases. To contain the spread of the coronavirus, governments, including in Israel, have restricted movements of their citizens which might have caused routine dental checkups to be postponed. Objective This study aimed to examin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…We found that a weekly dental selfie using the iGAM app reduced the signs of gingivitis and promoted oral health. These findings were published in part 2 of this series of articles [ 15 ].…”
Section: Introductionmentioning
confidence: 79%
“…We found that a weekly dental selfie using the iGAM app reduced the signs of gingivitis and promoted oral health. These findings were published in part 2 of this series of articles [ 15 ].…”
Section: Introductionmentioning
confidence: 79%
“…For medical apps, of the 11 definitions, 6 (55%) were published in German. As for health apps, most descriptions for medical apps came from Germany (7/11, 64%) or the United States (2/11, 18%), only 9% (1/11) came from Australia [ 71 ], and 9% (1/11) came from Canada [ 72 ]. b German publications translated by the authors (MF, HHD, and TJ) into English.…”
Section: Resultsmentioning
confidence: 99%
“…For health apps, the 2 dominant topics were the health aim of health apps and the used or produced data. Only a few definitions (2/22, 9%) addressed the missing regulation and the functions of the apps ( Multimedia Appendix 2 [ 21 , 35 , 48 , 51 , 53 - 58 , 60 - 66 , 68 - 72 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations